VEHICLE ROUTING PROBLEM WITH TIME WINDOWS (Perner's Contacts, 2011)
This paper is focus on solve the Vehicle Routing Problem with Time Windows. The each customer determine the number of requirements and the time of visit of vehicle in this contribution. The mathematical model for solve this problem was published by prof. RNDr. Jaroslav Janacek, CSc. and there is used in this contribution. The real problem of distribution of beer was solving through this mathematical model.
Keywords: transportation problem; vehicle routing problem; time windows